2023
DOI: 10.1038/s41586-022-05676-z
|View full text |Cite
|
Sign up to set email alerts
|

Deuterium-enriched water ties planet-forming disks to comets and protostars

Abstract: Springer Nature or its licensor (e.g. a society or other partner) holds exclusive rights to this article under a publishing agreement with the author(s) or other rightsholder(s); author self-archiving of the accepted manuscript version of this article is solely governed by the terms of such publishing agreement and applicable law.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 68 publications
3
27
0
Order By: Relevance
“…Loomis et al (2018) and van 't Hoff et al (2020) also showed a similar emission distribution for protoplanetary disks. The high-resolution images show a crescent shape of emission distribution with a central emission hole within r∼0 1 (Lee et al 2019b;Tobin et al 2023), but the elongated beam shape of SG3 distorts the emission distribution in the images used in this study. In addition, the central emission hole, which is produced by the optically thick dust emission, is also distorted by the elongated beam shape, resulting in the dip between two elongated…”
Section: Pc1-filtering Methodsmentioning
confidence: 65%
See 3 more Smart Citations
“…Loomis et al (2018) and van 't Hoff et al (2020) also showed a similar emission distribution for protoplanetary disks. The high-resolution images show a crescent shape of emission distribution with a central emission hole within r∼0 1 (Lee et al 2019b;Tobin et al 2023), but the elongated beam shape of SG3 distorts the emission distribution in the images used in this study. In addition, the central emission hole, which is produced by the optically thick dust emission, is also distorted by the elongated beam shape, resulting in the dip between two elongated…”
Section: Pc1-filtering Methodsmentioning
confidence: 65%
“…Various simple molecules and COMs have been detected, and it has been demonstrated that different molecules trace different kinematic components within V883 Ori. Among the detected lines, as presented in Tobin et al (2023), the HDO line is detected toward the inner region of the protoplanetary disk within the projected radius of ∼120 au (0 3), and the COMs' emission is confined within the water sublimation region. To identify all the detected COM lines and derive the physical conditions of the gas component associated with COM emission, high-S/N line spectra corrected for the kinematics are essential.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…In the region where the temperature exceeds that of water ice sublimation (∼120 K, which correspond to a radius of about 320 au in the case of V388), iCOMs trapped in the ice are injected into the gas-phase, like in the hot corinos (Section 3.2), and become observable along with water. 97–101 Not surprisingly, the detection of methanol, acetaldehyde, methyl formate and methyl cyanide have been reported. 98,99…”
Section: Observations Of Icoms and Ices In Solar-type Star Forming Re...mentioning
confidence: 99%